2010
DOI: 10.1017/s1751731109991595
|View full text |Cite
|
Sign up to set email alerts
|

In vitro methodology, hormonal and nutritional effects and fibre production in isolated ovine and caprine anagen hair follicles

Abstract: Mammalian hair follicles are complex multicellular structures in the skin, which produce hair fibre under the influence of locally produced and systemic signalling systems. Investigation to determine mechanisms of regulation, follicular responses and the importance of nutritional supply have utilised a number of in vivo and in vitro approaches. Included in these are studies on isolated intact anagen secondary follicles singly or in groups with incubation in culture medium. These utilise techniques developed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…Craven et al (2006) have identified, in skin and hair follicles of transgenic mice, local production of prolactin which is considered to interact with that present systemically. The addition of prolactin (200 mg/l) to culture medium been shown to stimulate both hair shaft elongation and protein synthesis in isolated cashmere and mohair anagen hair follicles (Galbraith, 2010). However, downstream effects of prolactin and potential interaction with, for example, paracrine regulators and pathways appear not to have been described.…”
Section: General Properties Of Integumental Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Craven et al (2006) have identified, in skin and hair follicles of transgenic mice, local production of prolactin which is considered to interact with that present systemically. The addition of prolactin (200 mg/l) to culture medium been shown to stimulate both hair shaft elongation and protein synthesis in isolated cashmere and mohair anagen hair follicles (Galbraith, 2010). However, downstream effects of prolactin and potential interaction with, for example, paracrine regulators and pathways appear not to have been described.…”
Section: General Properties Of Integumental Tissuesmentioning
confidence: 99%
“…The disparity between the concentrations of cysteine in hair fibre and that in sulphur amino acid supply are factors in the relatively low value (0.3) relating conversion of metabolisable protein to hair follicle protein in animals such as sheep (Agricultural and Food Research Council (AFRC), 1993). Additional factors of importance are transport in blood and uptake into follicles by mechanisms which are now becoming understood in integumental tissues including the hair follicle (Thomas et al, 2007;Hepburn et al, 2008;Galbraith, 2010). Post-absorptive utilisation depends on supply at the follicle level and synthetic activities of structures (particularly medulla: cortex, cuticle and IRS) according to position in the follicular cycle.…”
Section: Nutrientsmentioning
confidence: 99%
See 1 more Smart Citation
“…During moult, the hair number, diameter or growth intensity are modified (Galbraith, 2010b). While wild lamoids (guanaco, vicuñ a) are reported to shed annually (Fowler, 1998), adult male llamas kept under natural light and ambient conditions in Scotland have been reported as shedding only partially, with 30% to 50% of the fibres being shed over an extended period (Russel and Redden, 1994).…”
Section: Modification Of the Fleecementioning
confidence: 99%
“…The application of in vitro methodology, developed from studies on human HFs, to investigation of the regulation of fibre growth in small ruminants is the subject of the paper by Galbraith (2010a). This approach enables measurement of intrinsic growth and physiological/metabolic behaviour of individual, or groups of, isolated anagen HFs in culture media.…”
Section: European Association For Animal Production and Animal Fibre mentioning
confidence: 99%